2016
DOI: 10.1192/bjp.bp.116.185173
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to sympathies for violent protest and terrorism

Abstract: Independent of SVPT associations with depressive symptoms, some expressions of social connectedness (measured as life events and political engagement) are associated with a lower risk of SVPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…We are undertaking further research into which types of depressive symptoms are relevant, and comparing white British with Pakistani men and women to explore common factors relating to extremism. A recent analysis of this data shows that depressive symptoms increase sympathies for violent protest and terrorist a little, but surprisingly life events, especially bereavement and giving money to a charity, and to a less significant extent, political participation, are negatively correlated with sympathies; our interpretation is that social connectedness, even if expressed through loss, is protective ( Bhui, Silva, Topciu, & Jones, 2016).…”
Section: A Public Health Approachmentioning
confidence: 46%
“…We are undertaking further research into which types of depressive symptoms are relevant, and comparing white British with Pakistani men and women to explore common factors relating to extremism. A recent analysis of this data shows that depressive symptoms increase sympathies for violent protest and terrorist a little, but surprisingly life events, especially bereavement and giving money to a charity, and to a less significant extent, political participation, are negatively correlated with sympathies; our interpretation is that social connectedness, even if expressed through loss, is protective ( Bhui, Silva, Topciu, & Jones, 2016).…”
Section: A Public Health Approachmentioning
confidence: 46%
“…These additional symptoms were included to tackle speculation of relevance, despite there being little empirical evidence. 13,14 Our new analyses attempted to replicate previous work on different samples, with better measures of depressive diagnoses and extremism. We again considered other factors such as social, political and cultural influence which have been proposed as risk factors of extremist attitudes.…”
Section: Mental Illness and Extremismmentioning
confidence: 98%
“…13 Depressive symptoms explained a significant proportion of the association between life events and political engagement with extremist sympathies. 14 Building on our previous studies of extremist beliefs and depressive symptoms in Pakistani and Bangladeshi men and women, this article presents the findings from a new population cohort that compares Pakistani and White British people, who were assessed for ICD-10 diagnoses of depressive illness and of dysthymia rather than depressive symptoms. We also assessed symptoms of personality disorders, autism, generalised anxiety and post-traumatic stress disorder (PTSD).…”
Section: Mental Illness and Extremismmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent population study has identified the importance of democratic engagement (actions such as voting in local elections, signing a petition or paying fees to a charity or campaigning organisation) in reducing vulnerability to radical appeals (Bhui et al, 2016).…”
Section: Resultsmentioning
confidence: 99%